Musical Chairs: Preparing Extension Communication Units for Inevitable Change - Margaret Herring; Thomas Knecht; Ashley Wood; Carol Whatley; Erik Anderson; Ken Spelke (Journal of Applied Communications, 2006)
What happens when a new university administration doesn't know what Extension does or why an Extension communication unit exists? In this paper, a group of Extension administrators and faculty examines several reasons university administrators might seek to downsize Extension services or eliminate their communication units. This paper identifies strengths inherent in communication units that will help university administrators understand the importance and contributions of Extension communicators. The paper also explores how to prepare a communication unit for inevitable change, especially if there will be one less chair at the table when the music stops.